CONSTRUCTION OF ROAD SURFACES AND BASES USING COLD REGENERATION OF ASPHALT CONCRETE IN INSTALLATION - Едгоров Жамолиддин Намазович (American Journals, 2023)
In the article Highways are the most important part of the country's overall transport system, without which no sector of the economy can function. The level of development and technical condition of the road network significantly affect both the economic and social development of the country as a whole and its individual regions.
Keywords: maintenance, service life, harmful emissions, operation, road, road conditions.